Problem solving, loneliness, depression levels and associated factors in high school adolescents - Sahin, Ummugulsum (Pak J Med Sci, 2016)
OBJECTIVES: To determine problem solving, loneliness, depression levels and associated factors in high school adolescents. METHODS: This cross-sectional study was conducted in a city west of Turkey (Bursa) in a public high school and the population was 774 and the sampling was 394 students. Students to be included in the study were selected using the multiple sampling method. A personal Information Form with 23 questions, Problem Solving Inventory (PSI), Loneliness Scale (UCLA), Beck Depression Inventory (BDI) were used as data collection tools in the study. Basic statistical analyses, t-test, Kruskall Wallis-H, One Way Anova and Pearson Correlation test were used to evaluate the data. Necessary permissions were obtained from the relevant institution, students, parents and the ethical committee. RESULTS: The study found significant differences between “problem solving level” and family type, health assessment, life quality and mothers’, fathers’ siblings’ closeness level; between “loneliness level” and gender, family income, health assessment, life quality and mothers’, fathers’, siblings’ closeness level; between “depression level” and life quality, family income, fathers’ closeness level. CONCLUSION: Unfavorable socio-economic and cultural conditions can have an effect on the problem solving, loneliness and depression levels of adolescents. Providing structured education to adolescents at risk under school mental health nursing practices is recommended.